Characteristic Curves and Criterion of Critical Difference in Assessing the Informativeness of Markers of Renal Damage in Lithotripsy - R. S. Iskhakova; A. G. Gilmanov (Неотложная медицинская помощь, 2021)
Aim of study. Determination of the diagnostic significance of laboratory biomarkers of renal tissue damage in remote nephrolithotripsy in patients with urolithiasis.Material and methods. On the basis of the urology department of the Republican Clinical Hospital (Ufa), 35 patients with urolithiasis were examined, who underwent remote shock wave lithotripsy sessions. The laboratory parameters were determined in patients: the number of erythrocytes, leukocytes in the blood, the level of lipocalin and microalbumin in the urine, as well as alpha2-microglobulin and cystatin C in the blood serum. The control group included 14 healthy donors. To determine the diagnostic efficacy of biomarkers of renal injury, characteristic curves were plotted, and lipocalin level shifts were interpreted taking into account the data on the critical difference criterion value.Results. When studying the urinary level of lipocalin in patients with urolithiasis, it was found that the difference in the concentration of the biomarker in them and in healthy individuals is statistically insignificant (0.68 pg/ml versus 0.4 pg/ml). After the first session of extracorporeal lithotripsy, an increase in urinary excretion of lipocalin by 5 times is noted, after the second - by an additional 1.6 times, and after the third - by another 1.7 times (the differences are statistically significant). To analyze the prognostic efficiency of markers of renal injury, characteristic curves were plotted. The area under the ROC curve for lipocalin varied from 0.77 to 0.80 depending on the number of sessions, which indicates a high diagnostic efficiency of this biomarker. The determination of the criterion of critical difference (CCD) showed that an increase in the level of lipocalin in the urine after the first session of lithotripsy more than 2.1 times is statistically significant. The concentration of the specified biomarker in urine exceeding 4.5 pg/ml, 6 pg/ml and 10 pg/ml after the first, second and third sessions of lithotripsy, respectively, can be considered as a basis for changing treatment tactics (delaying the second procedure) or performing lithotripsy in another way.Conclusion. Urinary lipocalin, associated with neutrophil gelatinase, is an informative biomarker of renal injury in the assessment of complications associated with the lithotripsy procedure.